# Solve this:

Please find below the solution to the asked query:

In $\u2206$ QLM and $\u2206$ RNM

LM = NM ( Given )

QM = RM ( Given )

And

$\angle \mathrm{QLM}=\angle \mathrm{RNM}=90\xb0(\mathrm{Given}\mathrm{ML}\perp \mathrm{PQ}\mathrm{and}\mathrm{MN}\perp \mathrm{PR})$

So,

$\u2206$ QLM $\cong $$\u2206$ RNM ( RHL rule )

So,

**$\angle $ MQL = $\angle $ MRN ( BY CPCT )**

Now from above equation and from base angle theorem we can get in $\u2206$ PQR :

**PQ = PR ( Hence proved )**

Hope this information will clear your doubts about topic.

If you have any more doubts just ask here on the forum and our experts will try to help you out as soon as possible.

Regards

**
**